Legal Assessment of the Expiration of Evidence of Customary Land Ownership - Octavia, Elfira Zahwa; Masykur, Mohammad Hamidi; Fadli, Moh (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2025)
This article examines the legal uncertainty faced by holders of written evidence of former customary land ownership in Indonesia following Article 96(2) of Government Regulation No. 18 of 2021, which invalidates such documents five years after the regulation’s enactment. Framed within a normative juridical method and conceptual approach, this study analyzes constitutional principles, statutory law, and selected international instruments to assess the impact of the regulation on Indigenous peoples' rights. The lack of transitional mechanisms, such as extended validity periods or community-based evidentiary alternatives, creates legal exclusion and deepens structural inequality—particularly in rural areas where state-recognized documentation is rarely accessible. While the regulation aims to standardize land certification, it risks violating procedural fairness, legitimate expectations, and the protection of property rights as guaranteed by Articles 18B(2) and 28G(1) of the 1945 Constitution. The article argues that agrarian policy reform must adopt a rights-based and restorative framework, capable of accommodating non-formal, community-rooted proofs of ownership to uphold justice and inclusivity within Indonesia’s plural legal system.